The role of Pleistocene meltwater-controlled uranium leaching in assessing irradiation-induced alteration of organic matter and petroleum potential in the Tremadocian Koporie Formation (Western Russia). (15th January 2019) - Schulz, Hans-Martin; Yang, Shengyu; Panova, Elena; Bechtel, Achim
Abstract: The organic matter- and uranium-rich Tremadocian Koporie Formation (" Dictyonema Shale" as traditional informal unit; 6–14 wt.% TOC, 74–274 ppm uranium) was studied with respect to the spatial and temporal distribution of the uranium contents in the shale since deposition. It was the aim to unravel organic-inorganic interactions as results of α-particle irradiation due to the decay of 238 U and the consequences for the differential alteration of the organic matter and petroleum potential. A multi-method approach was applied to gain data on high resolution from electron microscopy, organic petrography, and organic and inorganic geochemistry about core samples from a borehole drilled 50 km southwest to St. Petersburg (Russia). The analytical results indicate that there were two sources of uranium. Bottom water anoxia promoted the reduction of soluble U(VI) from seawater (source 1) to U(IV) followed by adsorption in the sediment. This uranium portion is neither quantifiable on minerals nor on organic matter by EDX-SEM. Bottom water currents caused intercalations of coarser-grained intervals during deposition of the lower part of the Koporie Formation. These intervals include detrital uranium-rich apatite and zircon grains together with graptolite rhabdosomes which are also rich in uranium (source 2). Flushing of these permeable layers by meltwater during the Pleistocene (de)glaciation caused mobilization of U(VI) due to oxidation of formerly adsorbed quadrivalent uranium. The present uranium contents in the lower Koporie Formation are thus residues of formerly higher contents and indicate that stronger irradiation-induced destruction of the organic matter occurred during higher uranium contents before meltwater leaching during the Pleistocene. Today the organic matter of the lower part exhibits characteristics of a kerogen type III from the perspective of pyrolytic products with a rather Gas and Condensate potential whereas the upper part of the Koporie Formation still has the inherited signal of a kerogen type I/II with a Low-Wax Paraffinic Oil potential. Lithological and mineralogical heterogeneities in the lower part with locally strong irradiation are an alternative explanation for the stronger organic matter alteration.